T-minus: the race to the moon - Ottaviani, Jim.; Cannon, Kevin.; Cannon, Zander. (Aladdin, 2009)
The whole world followed the countdown to sending the first men to the moon. This is the story of the people who made it happen, both in the rockets and behind the scenes.
The whole world followed the countdown to sending the first men to the moon. This is the story of the people who made it happen, both in the rockets and behind the scenes.
Ages 8-12
A Junior Library Guild selection
Keywords: Graphic novels / United States.; Comic books, strips, etc. / United States.; Astronautics / Soviet Union / History / Comic books, strips, etc.; Astronautics / United States / History / Comic books, strips, etc.; Space race / History / Comic books, strips, etc.